REVITALISASI DESAIN INTERIOR MUSEUM KEBANGKITAN NASIONAL JAKARTA - Tunjung Atmadi (Institut Seni Indonesia Yogyakarta, 2018)
The existence of the Museum in general has not been able to optimally meet the needs of the community as a means of education and quality recreation. Ministry of Education and Culture (Kemdikbud) since 2011 has rolled out the Revitalization program of the Museum as an effort to improve the quality of the museum in serving the community and make the museum as a “need” to visit.Revitalization at the Museum of National Awakening encompasses the physical appearance of the museum made interesting, by arranging the interior, exterior, and rehabilitation of other supporting facilities. The method applied in this research is qualitative method, perform analysis based on case study data with the theory used.The result of this museum revitalization as a means of public learning, but also must be able to support the development of science. As an educational and academic function: the museum serves as a vehicle for education, a means of sharing knowledge and should be a center of study or a center of educational studies.